Contribution of eye excess energy to the intensification rate of tropical cyclones: A numerical study - Yuqing Wang; Junyao Heng (Journal of Advances in Modeling Earth Systems, 2016)
Abstract Contribution of the near‐surface high energy air in the eye region to tropical cyclone (TC) intensification rate (IR) has been evaluated based on idealized numerical experiments using a cloud‐resolving, nonhydrostatic atmospheric model. The results show that when the surface entropy flux was turned off in the eye region, the equivalent potential temperature and convective available potential energy in the eye were largely suppressed while the IR of the simulated storm was reduced by about 30% in the rapid intensification (RI) phase. This suggests that the near‐surface high energy air in the eye region contributed about 42% to the IR of the simulated storm. The results also showed that the number of convective bursts and the rainfall rate averaged in the inner‐core region did not display significant differences. This suggests that the effect of the near‐surface high energy air in the eye region on the simulated TC IR was not through the modifications to the overall strength of eyewall convection as previously hypothesized. It is found that the removal of surface entropy flux in the eye region resulted in a slower eyewall contraction and the larger radius of maximum wind (RMW). The results suggest that the near‐surface high energy air in the eye region can initiate convection near the inner edge of the eyewall and facilitates eyewall contraction, leading to higher inner‐core inertial stability and thus higher dynamical efficiency of eyewall heating in spinning up the tangential winds near the RMW and larger IR of the simulated TC.